The effect of 18O‐labelled water vapour on the oxygen isotope ratio of water and assimilates in plants at high humidity. Issue 1 (20th September 2017) - Lehmann, Marco M.; Goldsmith, Gregory R.; Schmid, Lola; Gessler, Arthur; Saurer, Matthias; Siegwolf, Rolf T. W.
Summary: Our understanding of how temporal variations of atmospheric water vapour and its isotopic composition (δ 18 OV ) influence water and assimilates in plants remains limited, restricting our ability to use δ 18 O as a tracer of ecophysiological processes. We exposed oak ( Quercus robur ) saplings under wet and dry soil moisture conditions to 18 O‐depleted water vapour ( c . − 200‰) at high relative humidity ( c . 93%) for 5 h, simulating a fog event. We then traced the step change in δ 18 OV into water and assimilates (e.g. sucrose, hexoses, quercitol and starch) in the leaf lamina, main veins and twigs over 24 h. The immediate δ 18 OV effect was highest for δ 18 O of leaf lamina water, but 40% lower on δ 18 O of main vein water. To a smaller extent, we also observed changes in δ 18 O of twig xylem water. Depending on the individual assimilation rate of each plant, the 18 O‐label was partitioned among different assimilates, with highest changes in δ 18 O of starch/sucrose and lowest in δ 18 O of quercitol. Additionally, 18 O‐label partitioning and allocation towards leaf starch and twig phloem sugars was influenced by the plant water status. Our results have important implications for water isotope heterogeneity in plants and for our understanding of how the δ 18 O signal is incorporated into biomarkers.